2021
DOI: 10.1016/j.heliyon.2021.e06734
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of polyphenolic compounds obtained from Euphorbia antisyphilitica by-products

Abstract: In this study, an alternative extraction technique, ultrasound-assisted extraction, was used to extract the polyphenolic fraction from two different residues of the candelilla plant ( Euphorbia antisyphilitica ). These metabolites were further analyzed to evaluate their bioactivity as antioxidants. In addition, their functional groups were identified by Fourier transform infrared (FTIR) spectroscopy. The antioxidant assays showed statistically significant differences between the phenolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 51 publications
1
12
0
Order By: Relevance
“…The presences of phenoloic, flavonoid and tannin compounds in the tested plants could be linked with the antioxidant properties of these extracts. This is consistent with the several recent studies, which suggested that the antioxidant properties could be referred to phenolic compounds present in plants [70]. Among the reported secondary metabolites in plants, phenolic components had been recognized as excellent substances for reducing the oxidative damage caused by the free radical in living cells [74].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The presences of phenoloic, flavonoid and tannin compounds in the tested plants could be linked with the antioxidant properties of these extracts. This is consistent with the several recent studies, which suggested that the antioxidant properties could be referred to phenolic compounds present in plants [70]. Among the reported secondary metabolites in plants, phenolic components had been recognized as excellent substances for reducing the oxidative damage caused by the free radical in living cells [74].…”
Section: Discussionsupporting
confidence: 90%
“…In previous studies, antioxidant activity was revealed in extracts from some species belong to the genus Euphorbia such as E. hirta, E. retusa and E. gaditana [70]. Mostafa et al [71] had reported that at concentration of 150 mg/ml, the ethyl acetate fraction from G. parviflora demonstrated strong antioxidant activity.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, after digestion, a significant decrease occurred, and no significant differences between the two series of samples (WG and MG) were observed. This result could be related to the overall antioxidant activity of a mixture of compound results from that of a single bioactive and its synergic effect [ 50 ]. Herbal infusions usually decrease their antioxidant activity after GID [ 31 , 44 , 47 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oil samples exposed at 160 °C during 120 h were analysed by Fourier transform infrared spectroscopy according to Bautista‐Hernández et al . (2021). Spectral data and functional groups detected were analysed using MicroLab Expert program, and the plot was constructed using Statistica 10 software (StatSoft, Tulsa, OK, USA).…”
Section: Methodsmentioning
confidence: 99%
“…In order to acquire information about the changes that could occur at the molecular level after the heating process of canola oil, without and with pomegranate peel polyphenols, infrared spectra were obtained. Oil samples exposed at 160 °C during 120 h were analysed by Fourier transform infrared spectroscopy according to Bautista-Hernández et al (2021). Spectral data and functional groups detected were analysed using MicroLab Expert program, and the plot was constructed using Statistica 10 software (StatSoft, Tulsa, OK, USA).…”
Section: Ft-ir Spectra Analysismentioning
confidence: 99%